2013
DOI: 10.5897/ajar11.2394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root restriction on vegetative growth and leaf anatomy of Kyoho grapevines cultivar

Abstract: The effects of root restriction on leaf and shoot growth and leaf anatomy of grape were investigated. Root restriction delayed leaf appearance, decreased leaf growth and reduced the rate of leaf expansion during all stage of berry development. Shoot growth of root-restricted vines was also reduced, with the length and thickness of shoots being lower than those of the control. Root restriction also induced adaptive changes in the leaf anatomy. Somata density of leaves from root-restricted vines was higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Due to this system, the roots are physically confined in a specific space, thus regulating vegetative and reproductive growth and improving fruit quality, and more plants can be planted in a given area. Several studies on grapes [ 23 25 ], cherry [ 26 ], carambola [ 27 ] and apple [ 28 ] have reported altered plant architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this system, the roots are physically confined in a specific space, thus regulating vegetative and reproductive growth and improving fruit quality, and more plants can be planted in a given area. Several studies on grapes [ 23 25 ], cherry [ 26 ], carambola [ 27 ] and apple [ 28 ] have reported altered plant architecture.…”
Section: Introductionmentioning
confidence: 99%